The nucleotide sequence of the ilvBN operon of Escherichia coli: sequence homologies of the acetohydroxy acid synthase isozymes. - Wek, R C (1985)
Three acetohydroxy acid synthase isozymes, AHAS I (ilvBN), AHAS II (ilvGM) and AHAS III (ilvIH) catalyze the first step of the parallel isoleucine-valine biosynthetic pathway in Escherichia coli. Previous DNA sequence and protein purification data have shown that AHAS II and AHAS III are composed of large and small subunits encoded in the ilvGMEDA and ilvIH operons, respectively. Recent protein purification and characterization data have demonstrated that the AHAS I isozyme is also composed of large and small subunits (L. Eoyang, L. and P. M. Silverman [1984] J. Bacteriol. 157:184-189). Now the complete DNA sequence of the operon encoding the AHAS I isozyme has been determined. These data show that both AHAS I subunits (Mr 60,400 and Mr 11,100) are encoded in this operon. The coordinant regulation of both genes of the ilvBN operon has also been demonstrated. Comparisons of the DNA sequences of the genes encoding all three AHAS isozymes have been performed. Conserved homologies were observed between both the large and small subunits of all three isozymes. The closest homology was seen between the AHAS I and AHAS II isozymes. On the basis of these comparisons a rationale for the evolution of the AHAS isozymes in E. coli has been proposed.